2015
DOI: 10.1007/s11999-014-3960-8
|View full text |Cite
|
Sign up to set email alerts
|

Does the Subtalar Joint Compensate for Ankle Malalignment in End-stage Ankle Arthritis?

Abstract: Background Patients with ankle arthritis often present with concomitant hindfoot deformity, which may involve the tibiotalar and subtalar joints. However, the possible compensatory mechanisms of these two mechanically linked joints are not well known. Questions/purposes In this study we sought to (1) compare ankle and hindfoot alignment of our study cohort with end-stage ankle arthritis with that of a control group; (2) explore the frequency of compensated malalignment between the tibiotalar and subtalar joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 28 publications
1
86
0
Order By: Relevance
“…Our intramedullary device combines the stiffness of intramedullary nail devices, while still using a minimally invasive approach, and obviates the need for a secondary surgery associated with the use of external fixation. Our new intramedullary device improves on the TTC nail by sparing the subtalar joint, which has been proposed to allow for compensation of the malalignment associated with worsening tibiotalar arthritis, and thus its importance cannot be overlooked [9]. When compared to traditional open approaches and the use of screws and plates our technique and device have less periosteal stripping.…”
Section: Discussionmentioning
confidence: 99%
“…Our intramedullary device combines the stiffness of intramedullary nail devices, while still using a minimally invasive approach, and obviates the need for a secondary surgery associated with the use of external fixation. Our new intramedullary device improves on the TTC nail by sparing the subtalar joint, which has been proposed to allow for compensation of the malalignment associated with worsening tibiotalar arthritis, and thus its importance cannot be overlooked [9]. When compared to traditional open approaches and the use of screws and plates our technique and device have less periosteal stripping.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,26,28 The MDTA is widely used to determine the amount and orientation of these supramalleolar deformities. 4,10,22,27,38,39,49,56 Incorrect assessment of the MDTA may result in under-or overcorrection that is associated with reduced outcomes following surgery. 5,6 Our study did not establish superiority of a single view to assess supramalleolar alignment.…”
Section: Clinical Significancementioning
confidence: 99%
“…In clinical practice, the MDTA is most often measured from an AP projection with 20 degrees of internal rotation of the foot (ie, mortise view). 4,27,38,49,56 We advocate for continued use of the mortise view, but given the finding that the MDTA on the AP view was sensitive to tilt of the x-ray beam, we would also recommend that technicians and clinicians adopt strategies to ensure that the beam is aligned directly with the horizon. This could be accomplished by resting the x-ray equipment on a flat, horizontal surface with the foot elevated at the correct height.…”
Section: Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Patients with post‐traumatic ankle osteoarthritis often present with a concomitant hindfoot deformity . In 2015, we analysed weightbearing radiographs of 226 patients with end‐stage, symptomatic ankle osteoarthritis and demonstrated that only 64.4% of all patients had a hindfoot alignment within normal range . Patients with concomitant ankle deformity – valgus or varus – and asymmetric ankle joint load may be vulnerable to asymmetric, premature cartilage damage.…”
mentioning
confidence: 99%